KEPEMIMPINAN PENDIDIKAN BERBASIS DATA SEBAGAI PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH DASAR - Widiansyah, Apriyanti; Fitriansyah, Fifit; Andini, Tiara Suci (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Improving the quality of education in elementary schools (SD) is a primary focus in the effort to create superior human resources. One effective strategy that is relevant to modern times is data-driven educational leadership, where strategic decisions are made based on accurate and relevant data analysis, not just on intuition. This research aims to explore the implementation, effectiveness, and challenges of data-driven leadership in improving the quality of education in elementary schools. The method used is a literature review, analyzing various literature, scientific journals, and documents related to educational leadership, data-based decision making, and quality improvement at the elementary school level. Data was collected systematically, followed by analysis to identify relevant patterns, findings, and best practices. The results show that data-driven leadership allows principals and teachers to identify areas needing improvement, design targeted interventions, and monitor student progress more objectively. This implementation has a positive impact on increasing student learning outcomes, improving learning effectiveness, and developing teacher competencies. However, its implementation faces challenges, such as a lack of data analysis skills, limited infrastructure, and resistance to changes in work culture. Data-driven leadership is a powerful approach for continuously improving educational quality in elementary schools. To maximize its potential, adequate training for educators, the provision of a reliable data management system, and full support from all stakeholders are needed. This approach can help elementary schools make more precise and evidence-based decisions, thus creating a higher-quality learning environment.